Savage ecology : war and geopolitics at the end of the world - Grove, Jairus Victor, 1978- (Duke University Press, 2019)
Jairus Victor Grove offers an ecological theorization of geopolitics in which he contends that contemporary global crises are better understood when considered within the larger history of geopolitical practice, showing how political violence is the principal force behind climate change, mass extinction, slavery, genocide, extractive capitalism, and other catastrophes.